(untitled) - Seymour Rosen (New York, 1977)
This book discusses the chemistry of metals and even more. It explains the tiny atoms and molecules that make up the things around us. This book tells about how different materials react with one another to form new materials. Ther aer exercises at the end of each lesson
Keywords: chemistry, physical and theoretical,metals